(3CUhd UfGYI GdSjGMI (B/s - (3GdWGFj, MejOs ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2001)
(3GdSjGMI ceaghe hadSaI,GdJWhQ GdJGQjNj dUfGYI GdSjGMI,GdYhGed GdeDKQI Ydi UfGYI GdSjGMI,GdYhGed GdGbJUGOjI,GdYhGed GdHjFjI,GdYhGed GdGLJeGYjI,eSJhjGJ GdJfXje aj UfGYI GdSjGMI,GdSjGMI GdeMdjI,Sdhc GdSGFM,JWhjQ efGWb GdLPH GdSjGMj,JWhjQ GdUhQI GdPgfjI Yf efGWb GdLPH GdSjGMj,GdJNWjW GdSjGMj,fXe GdeYdheGJ GdSjGMjI hOhQgG aj JWhjQ GdSjGMI(B((3OQGSI MGdI GdCQOf(B)s
Keywords: (3GdSjGMI (B- (3GbJUGOjGJs; (3GdSjGMI (B- (3GdGQOfs